Curriculum Analysis of the Undergraduate Program in Arabic Language Education at IAIN Pontianak: Relevance, Objectives, and Implementation - Khalil, Muhammad Amin; Sahri, Sahri; Hidayat, Moh Yusuf; Ramadhan, Ahmad Fadhail (International Journal of Islamic Thought and Humanities, 2025)
This research aims to analyze the curriculum of the Arabic Language Education Study Program at IAIN Pontianak, focusing on the aspects of relevance, objectives, and implementation. The study uses a descriptive qualitative approach with document analysis methods. Data is obtained from curriculum documents and the vision-mission of the study program, as well as analysis of student theses, to assess the alignment between academic policy directions and research practices. The analysis results show that the curriculum of the Arabic Language Education Study Program at IAIN Pontianak integrates the study of Arabic language education, religious values, and elements of Borneo culture, which are formulated in the vision, mission, objectives, course structure, and academic programs such as drama-based muhadatsah. This integration has become a characteristic that distinguishes this study program from other Arabic language education programs in Indonesia. However, weaknesses are still found in the selection of thesis topics by students, which generally focus on pedagogical issues and have not widely examined the cultural dimensions of Borneo. The limitation of this research lies in its scope, which is only based on document analysis without supporting field data. Further research is recommended to study the implementation of the curriculum through field studies in analyzing the curriculum.